2021
DOI: 10.2147/opth.s325394
|View full text |Cite
|
Sign up to set email alerts
|

Standalone Trabeculotomy and Viscodilation of Schlemm’s Canal and Collector Channels in Open-Angle Glaucoma Using the OMNI Surgical System: 24-Month Outcomes

Abstract: Purpose: Intraocular pressure (IOP), medication outcomes at 24 months following trabeculotomy/viscodilation using the OMNI® surgical system as a standalone procedure in medically uncontrolled mild-moderate open-angle glaucoma (OAG). Setting: Surgical center (Duesseldorf, Germany). Design: Retrospective analysis. IOP and medication data were collected before surgery and through 24 months. Safety data included adverse events and the need for additional surgery. Methods: Pre-op medication washout. Goldmann tonome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
(42 reference statements)
2
21
0
1
Order By: Relevance
“…These include the prospective, multicenter (US) GEMINI study which included a preoperative and terminal medication washout with 149 eyes undergoing OSS with phacoemulsification cataract surgery, 4 , 5 a single-center, prospective 12-month Polish study of standalone and combination procedures, 6 and a single-center German study with 24-month data for standalone cases that included both phakic and pseudophakic eyes. 7 The GEMINI study showed an IOP decrease of 8.2 mmHg (from 23.8 to 15.6 mmHg, −35%) from preoperative to month 12 (both unmedicated following medication washout) and medications decreased from 1.8 to 0.4. Comparison of the GEMINI patient demographics and glaucoma characteristics to those of the present study show that, on average, the GEMINI patients were somewhat younger (68.3 years vs 72.9 years), had slightly less advanced glaucoma (visual field MD −3.7 dB vs −4.5 dB), and were more uniformly POAG (93% vs 84% for the +cataract cohort).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These include the prospective, multicenter (US) GEMINI study which included a preoperative and terminal medication washout with 149 eyes undergoing OSS with phacoemulsification cataract surgery, 4 , 5 a single-center, prospective 12-month Polish study of standalone and combination procedures, 6 and a single-center German study with 24-month data for standalone cases that included both phakic and pseudophakic eyes. 7 The GEMINI study showed an IOP decrease of 8.2 mmHg (from 23.8 to 15.6 mmHg, −35%) from preoperative to month 12 (both unmedicated following medication washout) and medications decreased from 1.8 to 0.4. Comparison of the GEMINI patient demographics and glaucoma characteristics to those of the present study show that, on average, the GEMINI patients were somewhat younger (68.3 years vs 72.9 years), had slightly less advanced glaucoma (visual field MD −3.7 dB vs −4.5 dB), and were more uniformly POAG (93% vs 84% for the +cataract cohort).…”
Section: Discussionmentioning
confidence: 97%
“…5 In a retrospective case series, Klabe reported IOP at 12 and 24 months of 14.7 and 14.9 mmHg at 12 and 24 months on 0.4 and 0.5 medications, while Grabska-Liberek reported, in a prospective case series, IOP of 12.7 mmHg on 0.64 medications at 12 months. 6,7 IOP outcomes in patients treated with OSS show a remarkable consistency across studies, typically in the mid-teens. 8 There is more apparent variability in medication reduction outcomes, but this can, at least in part, be attributed to the use of a baseline medication washout in some of the studies.…”
mentioning
confidence: 90%
“…Klabe et al evaluated postoperative outcomes of 38 eyes after standalone ab interno canaloplasty and trabeculotomy reporting a hyphema rate of 44.7% with none being >1 mm. 15 Comparatively, only 4.2% of eyes included in the ROMEO study experienced clinically significant hyphema defined as layered and >1 mm and/or persisting >1 week and/or requiring secondary intervention. 13 Only 2 eyes (3.0%) required additional surgery for IOP.…”
Section: Discussionmentioning
confidence: 93%
“…These findings parallel prior studies, which reported similar reductions in IOP and medication burden sustained out to 12 and 24-months. 13 , 15 However, a key point of distinction is this study’s inclusion of pseudophakic eyes with severe glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation